(3JWHjbGJ JcfhdhLjG GdeYdheGJ aj GdCYeGd (B:s (3eONd JShjbj (B/s - (3GdYdGb, HTjQ YHGSs ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2002)
(3OhQ GdESJQGJjLj dJcfhdhLjG GdeYdheGJ(B- (3JWHjbGJ JcfhdhLjG GdeYdheGJ aj UfGYI GdNOeGJ(B- (3fXe ESfGO hJWhjQ bQGQGJ hESJQGJjLjGJ GdJShjbs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3JcfhdhLjG GdeYdheGJs